Tobacco Advertisements: What Messages Are They Sending in African American Communities?. Issue 1 (January 2020) - Rosario, Carrie; Harris, Keia E.
Racial disparities in tobacco-related death and disease persist. Despite evidence of disparities in exposure to tobacco retailers and point-of-sale advertising, little is known about the extent to which tobacco advertisements within African American communities use three prominent messaging strategies: reassure use is safe despite health risks, redirect attention from health risks to other product features, or incite bravery to use despite health risks. Using a multistage design, we examined tobacco advertisements at 24 retail stores listed onCountertools.org StoreMapper within 15 census tracts where roughly 74% of the population was African American. After confirming interrater reliability, trained data collectors assessed messaging strategy (reassurance, misdirection of attention, or inducement to bravery) usage in ads (n = 165) for various brands (e.g., Newport, Swisher Sweets, Blu) and whether strategies varied by product type (e.g., cigarettes, nonlarge cigar, e-cigarettes). Chi-square analysis of 165 advertisements revealed that the misdirection of attention strategy was used more often than reassurance or inducement to bravery. Tobacco advertisement messaging strategies also varied by product type, with misdirection of attention used more frequently in cigarette and nonlarge cigar advertisements and reassurance used more frequently in e-cigarette advertisements. Cigarette and nonlarge cigar advertisement messages prey on African American communities by redirecting their focus from consequences toward favorable product attributes. Additionally, reassurance messaging may misconstrue risks associated with e-cigarettes; therefore, we should vigilantly monitor e-cigarette trends among this population. Countering misleading messages and advocating policies regarding advertisement content and density within African American communities could help reduce health disparities.